Water-Extracted Prunella vulgaris Alleviates Endometriosis by Reducing Aerobic Glycolysis - Cho, Min Kyoung; Jin, Ling; Han, Jung Ho; Jin, Jung-Suk; Cheon, Se-Yun; Shin, Su; Bae, Sung-Jin; Park, Jang-Kyung; Ha, Ki-Tae (Frontiers in Pharmacology, 2022)
Endometriosis is a chronic inflammatory disorder caused by abnormal adhesion of endometrial tissue to the outside of the uterus. The combination of surgery, non-steroidal anti-inflammatory drugs, and hormone treatment is well established therapy for endometriosis, however, case reports have showed that high rates of relapse and unpleasant side effect. For these reasons, recently, the studies have been focused on the Warburg-like metabolic shift of endometriosis. Prunella vulgaris is one of traditionally used herbal medicine for inflammatory disease and the anti-estrogenic effects of P. vulgaris is well-established. Therefore, in this work, we evaluated water-extracted P. vulgaris (PV) as a potential treatment for endometriosis. To this, we artificially induced endometriosis in ovarectomized mice by intra-peritoneal inoculation of uterus extracts. PV was orally administered, and PV significantly alleviated endometriosis, particularly the growth of ectopic endometrial lesions in artificially endometriosis-induced mice. For the mechanism study of anti-endometriosis by PV, we designed an in vitro study using human normal endometrial stromal cells (T-HESCs) and human endometrial cell (12Z) obtained from patients with endometriosis. PV strongly induced the apoptosis of 12Z cells rather than T-HESCs by control the activity or expression of aerobic glycolysis enzymes, such as LDHA, PDHA, and PDK1/3. In addition, lactate production was enhanced, and OCR was suppressed in 12Z cells upon PV treatment. These changes in aerobic glycolysis eventually caused mitochondrial damage following decreased MMP and excessive mitoROS production. Especially, ulsolic acid (UA), one of the compounds in PV considerably led 12Z cell apoptosis with inhibition of LDHA activity. Therefore, UA could be a major active substance of PV in terms of endometriosis inhibitors. In conclusion, this study provides the evidence that the beneficial efficacy of PV for the prevention/treatment of endometriosis.